Methodological approaches to evaluation in breastfeeding rates of Chechen Republic and Republic of Ingushetia - L. V. Abolyan; P. M. Evloeva (Сеченовский вестник, 2013)
The complex medical and social assessment of the prevalence and duration of breastfeeding in the Chechen Republic and the Republic of Ingushetia based on a survey of mothers of children aged 12–36 months was made. It was founded that the duration of breastfeeding has an impact, first of all, a positive women’s attitude to breastfeeding or dominant lactation and duration of exclusive breastfeeding. The increase of the duration of breastfeeding leads to the introduction of modern medical and organizational measures to protect and support breastfeeding in maternity and child care institutions.